SANKSI PIDANA BAGI ANAK YANG MELAKUKAN PENCURIAN DENGAN PEMBERATAN (ANALISIS PUTUSAN NOMOR: 1/Pid.Sus-Anak/2024/Pn.Mtw) - Tri Muryani, Imelda; Ucuk Suyono, Yoyok; Subketi, Subketi; Prawesthi, Wahyu (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study analyzes criminal sanctions for juvenile offenders committing aggravated theft based on Decision No. 1/Pid.Sus-Anak/2024/PN.Mtw amid a surge in juvenile delinquency cases reaching 14,000 in the first semester of 2025, driven by economic, social, and peer influences, where child protection principles often conflict with imprisonment despite the Juvenile Justice System Law (UU SPPA) promoting restorative justice; its objective is to examine the application of these principles and the judge's ratio decidendi with recommendations for optimization. Employing a normative legal approach (statute and case methods) with qualitative descriptive analysis, the population encompasses all child protection regulations and district court decisions across Indonesia, purposively sampling the Muara Teweh decision; instruments include primary documents (laws, rulings, Litmas reports) and secondary literature, analyzed descriptively through description, classification, and interpretation. Findings reveal procedural compliance (identity protection, legal assistance, Litmas) but substantive shortcomings due to a 3-month reduced prison sentence, with diversion hindered by the 7-year threat under Article 363 of the Criminal Code; the judge's ratio decidendi integrates juridical, factual, and philosophical considerations prioritizing the best interest of the child via LPKA guidance, recommending non-custodial alternatives and diversion threshold revisions.